2002
DOI: 10.1097/00043764-200206000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Health in the Construction Industry?

Abstract: The construction industry has long been regarded as a high-risk industry in relation to health and safety issues. The purpose of this research was to investigate the extent of occupational health and safety provision within the residential development sector of the construction industry in Britain. An additional aim was to gauge the sectors' attitudes toward health promotion. Data were collected using a self-completed questionnaire that was sent to 200 residential developers; a 46% response rate was achieved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Males and young people have been identified in other contexts as tending towards reporting lower risk appraisals and higher coping appraisals 15,16) . Furthermore, young people are more likely than older adults to value the perceived short-term benefits of sun tanning and hold misconceptions about personal resilience to sundamage 13) . Studies of sun-protection behaviors in other populations have found evidence of optimistic bias when assessing the personal risks associated with excess sun exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Males and young people have been identified in other contexts as tending towards reporting lower risk appraisals and higher coping appraisals 15,16) . Furthermore, young people are more likely than older adults to value the perceived short-term benefits of sun tanning and hold misconceptions about personal resilience to sundamage 13) . Studies of sun-protection behaviors in other populations have found evidence of optimistic bias when assessing the personal risks associated with excess sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to demographic factors, such as age group, gender and ethnicity, other personal and workplace factors are likely to contribute to outdoor workers' perceptions of workplace sun-exposure and perceptions of risk of developing skin cancer 12,13) . Workplace cultures and sun protection policies are likely to play a role in shaping risk perceptions and sun protection use 13) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This 'critical mass' of smokers as a group, may become strongly resistant to antismoking measures, regardless of their benefits for any one individual. Previous research among construction workers in the US for example 84) , has suggested that there may be a low level of health promotion policy development with regard to smoking. As support will clearly be needed 'at the coal face', an expanded role for labor unions in the development of more healthy lifestyle practices for their constituents, would be a step in the right direction.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] The interviewees commented on the smoking and alcohol restrictions on sites, which confirms the findings by Pritchard and McCarthy. 36 The issues brought up during the discussions related to the manager's role and problems with adhering to the restrictions.…”
Section: Discussionmentioning
confidence: 99%